Maleimide copolymer, method for producing the same, and resin composition using the maleimide copolymer
By preparing the co -concentration of the Malayside and mixed with specific resin, the problem of decreased surface gloss in the process of shooting the heat -resistant ABS resin is solved. The balance of sex is suitable for applications such as automotive components.
Patent Information
- Application Number
- CN202080023669.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-10
- Filing Date
- 2020-07-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-07-07
AI Technical Summary
During the injection molding process of the conventional heat-resistant ABS resin, the surface gloss is easily reduced, and it is difficult to maintain impact resistance, heat resistance and flowability at the same time.
Maleimide copolymers are used to copolymerize aromatic vinyl monomers, cyanide vinyl monomers, maleimide monomers and dicarboxylic anhydride monomers, and then imidize the two monomers. Carboxylic anhydride monomer units are converted into maleimide monomer units to prepare copolymers with specific glass transition temperatures and average values of dicarboxylic anhydride monomer units. The copolymer is mixed with ABS resin, ASA resin, AES resin or SAN resin to form a resin composition.
While maintaining impact resistance, heat resistance, and liquidity, it has significantly improved the surface gloss of the forming shape, and is suitable for applications such as car interior or outer components.
Smart Images

Figure BDA0003275105910000171 
Figure BDA0003275105910000181 
Figure BDA0003275105910000211
Abstract
Description
Technical Field
[0001] The present invention relates to a maleimide copolymer, a method for producing the same, and a resin composition using the maleimide copolymer. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer resin (ABS resin) has excellent mechanical strength, appearance, chemical resistance, moldability, etc., and is widely used in the fields of automobiles, home appliances, OA equipment, residential building materials, daily necessities, etc. For applications such as automotive interior materials that require heat resistance, ABS resin containing maleimide-based copolymers (heat-resistant ABS) is also used as a heat resistance imparting agent (for example, Patent Document 1, Patent Document 2).
[0003] In order to further impart chemical resistance to heat-resistant ABS, heat-resistant agents obtained by copolymerizing maleimide copolymers with vinyl cyanide monomers have been proposed (e.g., Patent Documents 3 and 4). These heat-resistant agents have no problem in normal use. However, when a mixed resin of a heat-resistant agent and ABS is injection molded, the surface glossiness of the resulting injection molded body may be reduced depending on the conditions.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 57-98536
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 57-125242
[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-339280
[0009] Patent Document 4: Japanese Patent Application Publication No. 2007-9228 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The present invention provides a maleimide copolymer and a method for producing the same, which can obtain a molded body with high surface gloss while maintaining impact resistance, heat resistance and fluidity. In addition, the present invention provides a resin composition obtained by kneading and mixing a maleimide copolymer with one or more resins selected from ABS resin, acrylonitrile-styrene-acrylic rubber copolymer resin (ASA resin), acrylonitrile-ethylene·propylene rubber-styrene copolymer resin (AES resin) or styrene-acrylonitrile copolymer resin (SAN resin), and the resin composition can obtain a molded body with high surface gloss while maintaining impact resistance, heat resistance and fluidity.
[0012] Technical means to solve the problem
[0013] That is, the present invention has the following gist.
[0014] (1) A maleimide copolymer comprising 40 to 60% by weight of an aromatic vinyl monomer unit, 5 to 20% by weight of a vinyl cyanide monomer unit, 25 to 50% by weight of a maleimide monomer unit, and 0.1 to 10% by weight of a dicarboxylic anhydride monomer unit, wherein the glass transition temperature of the maleimide copolymer is 165° C. to 200° C., and the average number of dicarboxylic anhydride monomer units contained in one molecule of the copolymer is 1 to 30.
[0015] (2) The method for producing a maleimide copolymer as described in (1), comprising the following steps:
[0016] Initial polymerization step: all of the vinyl cyanide monomer feed amount, 10 to 90% by weight of the aromatic vinyl monomer feed amount, and 0 to 30% by weight of the unsaturated dicarboxylic acid anhydride monomer feed amount are mixed to initiate copolymerization;
[0017] Mid-term polymerization step: adding 50-90% by weight of the remaining aromatic vinyl monomer and all of the remaining unsaturated dicarboxylic anhydride monomer in batches or continuously, and continuing copolymerization;
[0018] Final polymerization step: adding all the remaining amount of the aromatic vinyl monomer to obtain a copolymer having an aromatic vinyl monomer unit, a cyanide vinyl monomer unit, and a dicarboxylic anhydride monomer unit; and
[0019] In the imidization step, the dicarboxylic anhydride monomer units of the obtained copolymer are imidized into maleimide monomer units using ammonia or a primary amine.
[0020] (3) A resin composition comprising 5 to 40% by mass of the maleimide copolymer described in (1) and 60 to 95% by mass of a resin, wherein the resin is one or more selected from ABS resin, ASA resin, AES resin or SAN resin.
[0021] (4) An injection-molded article using the resin composition described in (3).
[0022] (5) The injection-molded article according to (4), which is used as an interior part or exterior part of an automobile.
[0023] Effects of the Invention
[0024] According to the present invention, a maleimide copolymer is provided, which can obtain a molded body with high surface gloss while maintaining impact resistance, heat resistance and fluidity, and a method for producing the same. In addition, a resin composition is provided, which is obtained by kneading and mixing the maleimide copolymer with one or more resins selected from ABS resin, ASA resin, AES resin or SAN resin, and the resin composition can obtain a molded body with high surface gloss while maintaining impact resistance, heat resistance and fluidity. DETAILED DESCRIPTION
[0025] <Terminology>
[0026] In this specification, the description "A to B" means A or more and B or less.
[0027] The maleimide copolymer of the present invention is not only a maleimide copolymer obtained by copolymerizing an aromatic vinyl monomer, a cyanide vinyl monomer, a maleimide monomer and an unsaturated dicarboxylic anhydride monomer, but also includes a maleimide copolymer obtained by copolymerizing an aromatic vinyl monomer, a cyanide vinyl monomer and an unsaturated dicarboxylic anhydride monomer and then imidizing the dicarboxylic anhydride monomer unit derived from the unsaturated dicarboxylic anhydride monomer in the molecule using ammonia or a primary amine.
[0028] The aromatic vinyl monomer used for the maleimide copolymer is a monomer that improves the hue of the resin composition, and includes, for example, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, α-methylstyrene, and α-methyl-p-methylstyrene. Among them, styrene is preferred because it has a good effect of improving the hue. The aromatic vinyl monomers may be used alone or in combination of two or more.
[0029] The amount of the aromatic vinyl monomer unit contained in the maleimide copolymer is 40 to 60% by mass, preferably 45 to 55% by mass. Specifically, for example, it is 40, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 60% by mass, or it can be within the range between any two values exemplified here. If the amount of the aromatic vinyl monomer unit is less than 40% by mass, the hue of the resin composition is yellowish, and if it is greater than 60% by mass, the heat resistance of the resin composition is reduced.
[0030] The vinyl cyanide monomer used in the maleimide copolymer is a monomer that improves the chemical resistance of the resin composition, and includes, for example, acrylonitrile, methacrylonitrile, ethacrylonitrile, and fumaronitrile. Among them, acrylonitrile is preferred because it has a good effect of improving chemical resistance. The vinyl cyanide monomer can be used alone or in combination of two or more.
[0031] The amount of the cyanide vinyl monomer unit contained in the maleimide copolymer is 5 to 20% by mass, preferably 7 to 15% by mass. Specifically, for example, it is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20% by mass, or it may be in the range between any two of the values exemplified here. If the amount of the cyanide vinyl monomer unit is less than 5% by mass, the effect of improving the chemical resistance of the resin composition cannot be obtained, and if it is greater than 20% by mass, the hue of the resin composition becomes yellowish.
[0032] The maleimide monomer that can be used for the maleimide copolymer is a monomer used to improve the heat resistance of the resin composition, for example, there are N-alkyl maleimides such as N-methyl maleimide, N-butyl maleimide, and N-cyclohexyl maleimide; and N-phenyl maleimide, N-chlorophenyl maleimide, N-methylphenyl maleimide, N-methoxyphenyl maleimide, and N-tribromophenyl maleimide. Among them, N-phenyl maleimide is preferred because it has a good effect of improving heat resistance. The maleimide monomers can be used alone or in combination of two or more.
[0033] The amount of maleimide monomer units contained in the maleimide copolymer is 25 to 50% by mass, preferably 37 to 45% by mass. Specifically, for example, 25, 30, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50% by mass, or within the range of any two values exemplified herein. If the amount of maleimide monomer units is less than 25% by mass, the effect of improving the heat resistance of the resin composition cannot be obtained, and if it is greater than 50% by mass, the impact strength of the resin composition is reduced.
[0034] The unsaturated dicarboxylic anhydride monomer used for the maleimide copolymer is a monomer used to improve the compatibility of the maleimide copolymer with ABS resin, etc., and includes maleic anhydride, itaconic anhydride, citraconic anhydride, and aconitic anhydride. Among them, maleic anhydride is preferred from the viewpoint of compatibility with ABS resin, etc. The unsaturated dicarboxylic anhydride monomer can be used alone or in combination of two or more.
[0035] The amount of the dicarboxylic anhydride monomer unit contained in the maleimide copolymer is 0.1 to 10% by mass, preferably 0.1 to 5% by mass, and more preferably 0.1 to 2% by mass. Specifically, for example, it is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10% by mass, and can also be in the range between any two values exemplified here. If the amount of the dicarboxylic anhydride monomer unit is less than 0.1% by mass, the effect of improving the compatibility with ABS resins and the like cannot be obtained. If it is greater than 10% by mass, the thermal stability of the resin composition is reduced.
[0036] The content ratios of the aromatic vinyl monomer unit, the vinyl cyanide monomer unit, the maleimide monomer unit and the dicarboxylic anhydride monomer unit contained in the maleimide copolymer are determined by 13 The values were measured by C-NMR method under the following measurement conditions.
[0037] Device name: FT-NMR AVANCE300 (BRUKER)
[0038] Solvent: deuterated chloroform
[0039] Concentration: 14% by mass
[0040] Temperature: 25℃
[0041] Cumulative times: 10,000 times
[0042] The weight average molecular weight of the maleimide copolymer is 50,000 to 300,000, preferably 50,000 to 200,000. Specifically, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 300,000, or within the range between any two of the values exemplified herein. If the weight average molecular weight is within the range of 50,000 to 300,000, the difference in melt viscosity with the acrylonitrile-butadiene-styrene copolymer resin, acrylonitrile-styrene-acrylic rubber copolymer resin, acrylonitrile-ethylene·propylene rubber-styrene copolymer resin or styrene-acrylonitrile copolymer resin described later is small, and the dispersibility with these resins is excellent.
[0043] The average number of dicarboxylic anhydride monomer units contained in one molecule of the maleimide copolymer is 1 to 30, preferably 1 to 20, and more preferably 4 to 15. Specifically, for example, it is 1, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30, or may be within the range between any two of the values exemplified herein. If the average number of dicarboxylic anhydride monomer units is less than 1, the effect of the dicarboxylic anhydride monomer units acting as a compatibilizer by reacting with other resins having amino or alcohol groups at the end is reduced, and if it exceeds 30, it is possible to react with metal salts derived from emulsion polymerization, amines used as additives, and generate crosslinked products.
[0044] In order to increase the average value of the dicarboxylic anhydride monomer units contained in one molecule of the maleimide-based copolymer, the weight average molecular weight may be increased or the amount of the dicarboxylic anhydride monomer units contained in the maleimide-based copolymer may be increased.
[0045] The average value of the dicarboxylic anhydride monomer units contained in one molecule of the maleimide-based copolymer is a value measured by the method shown below.
[0046] (1. Determination of weight average molecular weight)
[0047] First, the weight average molecular weight of the maleimide copolymer is measured by the GPC method under the following measurement conditions.
[0048] Device name: SYSTEM-21 Shodex (manufactured by Showa Denko K.K.)
[0049] Column: 3 PL gel MIXED-B connected in series
[0050] Temperature: 40℃
[0051] Detection: Differential refractive index
[0052] Solvent: Tetrahydrofuran
[0053] Concentration: 0.8 mass%
[0054] Standard curve: drawn using standard polystyrene (PS) (manufactured by PL).
[0055] (2. Amount of dicarboxylic anhydride monomer units)
[0056] Next, the content of the dicarboxylic anhydride monomer unit contained in the maleimide copolymer was determined by colorimetric titration of a methyl ethyl ketone solution of the maleimide copolymer with a 0.1 N ethanolic potassium hydroxide solution (indicator: phenolphthalein).
[0057] A: Mass of maleimide copolymer (g)
[0058] B: Blank value of the volume of the added ethanolic potassium hydroxide solution (mL)
[0059] C: Volume of ethanolic potassium hydroxide solution added (mL)
[0060] D: molar mass of dicarboxylic anhydride monomer unit
[0061] The content (mass %) of the dicarboxylic anhydride monomer unit contained in the maleimide-based copolymer can be calculated from the following formula (1).
[0062] (CB)×D / A / 100…(1)
[0063] (3.1 Average value of dicarboxylic anhydride monomer units in the molecule)
[0064] The average value of the dicarboxylic anhydride monomer units in one molecule of the maleimide copolymer can be calculated from the weight average molecular weight (E) calculated above and the content (F) of the dicarboxylic anhydride monomer units in the maleimide copolymer according to the following formula (2).
[0065] E×F / D / 100…(2)
[0066] The maleimide copolymer of the present invention can also be obtained by copolymerizing the above-mentioned aromatic vinyl monomer, vinyl cyanide monomer and unsaturated dicarboxylic anhydride monomer, and then converting the dicarboxylic anhydride monomer unit in the copolymer into a maleimide monomer unit by imidization with ammonia or a primary amine (post-imidization method).
[0067] The so-called primary amines include alkylamines such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, n-pentylamine, n-hexylamine, n-octylamine, cyclohexylamine, and decylamine, as well as chlorine or bromine substituted alkylamines; aromatic amines such as aniline, toluidine, and naphthylamine, among which aniline and cyclohexylamine are preferred. These primary amines can be used alone or in combination of two or more. The amount of primary amine added is not particularly limited, and is preferably 0.7 to 1.1 molar equivalents relative to the dicarboxylic anhydride monomer unit, and more preferably 0.85 to 1.05 molar equivalents. If it is 0.7 molar equivalents or more relative to the dicarboxylic anhydride monomer unit in the maleimide copolymer, the thermal stability of the obtained resin composition is good, so it is preferred. In addition, if it is 1.1 molar equivalents or less, the amount of primary amines remaining in the maleimide copolymer is reduced, so it is preferred.
[0068] When obtaining a maleimide copolymer, in the reaction of ammonia or primary amine with a dicarboxylic anhydride monomer unit, especially in the reaction of converting a dicarboxylic anhydride monomer unit into a maleimide monomer unit, a catalyst may be used as needed for the purpose of improving the dehydration ring-closing reaction. The type of catalyst is not particularly limited, and for example, a tertiary amine can be used. As tertiary amines, for example, trimethylamine, triethylamine, tripropylamine, tributylamine, N, N-dimethylaniline, N, N-diethylaniline, etc. can be cited. The amount of tertiary amine added is not particularly limited, and is preferably 0.01 molar equivalent or more relative to the dicarboxylic anhydride monomer unit. The temperature of the imidization reaction in the present invention is preferably 100 to 250°C, and more preferably 120 to 200°C. If the temperature of the imidization reaction is above 100°C, the reaction rate is sufficiently fast, which is preferred from the perspective of productivity. If the temperature of the imidization reaction is below 250°C, it is possible to suppress the reduction in physical properties caused by thermal degradation of the maleimide copolymer, and thus it is preferred.
[0069] When obtaining maleimide copolymer, aromatic vinyl monomer, cyanide vinyl monomer, unsaturated dicarboxylic acid anhydride monomer can also be all put into polymerization in the initial stage of polymerization, but the alternating copolymerization of aromatic vinyl monomer and unsaturated dicarboxylic acid anhydride monomer is strong, so aromatic vinyl monomer and unsaturated dicarboxylic acid anhydride monomer will be consumed in the early stage of polymerization, and copolymer with many cyanide vinyl monomer units is easily generated in the later stage of polymerization. As a result, the hue and phase of the obtained maleimide copolymer sometimes deteriorate, or the composition distribution becomes larger, and the miscibility when mixing with ABS resins is insufficient, resulting in the poor physical properties of the obtained resin composition. Therefore, in order to obtain a maleimide copolymer with good hue and phase and small (uniform) composition distribution, it is preferred to use a manufacturing method with the following steps.
[0070] Initial polymerization step: The entire amount of the vinyl cyanide monomer, 10 to 90% by weight of the aromatic vinyl monomer, and 0 to 30% by weight of the unsaturated dicarboxylic acid anhydride monomer are mixed and added at the initial stage of polymerization to initiate copolymerization.
[0071] Mid-term polymerization step: the remaining amount of the aromatic vinyl monomer and the remaining amount of the unsaturated dicarboxylic anhydride monomer are added in batches or continuously, and copolymerization is continued at the same time.
[0072] Final polymerization step: After all the unsaturated dicarboxylic acid anhydride monomers are charged, 1 / 10 or more of the batch or continuous addition amount of the aromatic vinyl monomer is added to carry out polymerization.
[0073] Imidization step: The obtained copolymer is imidized with ammonia or a primary amine to obtain a maleimide copolymer.
[0074] The method for removing the volatile components such as the solvent or unreacted monomers used in the solution polymerization from the solution after the imidization process of the maleimide copolymer is completed (devolatilization method) can be a known method. For example, a vacuum devolatilization tank with a heater or a devolatilization extruder with an air outlet can be used. The maleimide copolymer in a molten state after devolatilization can be transferred to a granulation process, extruded in a linear form from a porous die head, and processed into granules by cold cutting, aerial hot cutting, or underwater hot cutting.
[0075] From the perspective of effectively improving the heat resistance of ABS resin, ASA resin and other mixed resins, the glass transition temperature of the maleimide copolymer is preferably 165°C to 200°C, more preferably 170°C to 200°C, and further preferably 175°C to 185°C. Specifically, for example, it is 165, 170, 175, 176, 177, 178, 179, 180, 185, 190, 195, 200°C, and can also be within the range between any two values exemplified here. The glass transition temperature is the glass transition midpoint temperature (Tmg) of the maleimide copolymer measured according to JIS K-7121 using the following apparatus and measurement conditions.
[0076] Device name: Differential Scanning Calorimeter Robot DSC6200 (manufactured by Seiko Instruments Ltd.)
[0077] Heating rate: 10℃ / min
[0078] In order to increase the glass transition temperature of the maleimide-based copolymer, the content of the maleimide monomer unit may be increased, or a monomer having a high glass transition temperature may be copolymerized.
[0079] In the range that does not hinder the effect of the present invention, the maleimide copolymer can also be copolymerized with copolymerizable monomers other than aromatic vinyl monomers, vinyl cyanide monomers and unsaturated dicarboxylic anhydride monomers. As monomers copolymerizable with the maleimide copolymer, N-alkyl maleimides such as N-methylmaleimide, N-butylmaleimide, and N-cyclohexylmaleimide, N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-methoxyphenylmaleimide, and N-tribromophenylmaleimide can be cited as maleimide monomers; acrylate monomers such as methyl acrylate, ethyl acrylate, and butyl acrylate, methacrylate monomers such as methyl methacrylate and ethyl methacrylate, vinyl carboxylic acid monomers such as acrylic acid and methacrylic acid, acrylic acid amide, and methacrylic acid amide, etc. Monomers copolymerizable with the maleimide copolymer can be used alone or in combination of two or more.
[0080] The polymerization methods of maleimide copolymers include solution polymerization and bulk polymerization. From the perspective of obtaining a maleimide copolymer with uniform copolymer composition by adding the monomers to be copolymerized in batches or continuously, solution polymerization is preferred. From the perspective of being less likely to produce by-products and having fewer adverse effects, the solvent for solution polymerization is preferably a non-polymerizing solvent, including ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and acetophenone; ethers such as tetrahydrofuran and 1,4-dioxane; aromatic hydrocarbons such as benzene, toluene, xylene, and chlorobenzene; N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc. From the perspective of the ease of solvent removal when devolatilizing and recovering maleimide copolymers, methyl ethyl ketone and methyl isobutyl ketone are preferred. Regarding the polymerization process, continuous polymerization, intermittent (batch) and semi-intermittent are all applicable.
[0081] The polymerization method of the maleimide copolymer is not particularly limited, but it can be preferably obtained by free radical polymerization, and the polymerization temperature is preferably in the range of 80 to 150°C. As the polymerization initiator, it is not particularly limited, for example, known azo compounds such as azobisisobutyronitrile, azobiscyclohexanecarbonitrile, azodimethylpropionitrile, and azodimethylbutyronitrile can be used; known organic peroxides such as benzoyl peroxide, tert-butyl peroxybenzoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy 2-ethylhexanoate, di-tert-butyl peroxide, dicumyl peroxide, and ethyl 3,3-di(tert-butylperoxy)butyrate can be used, and one of these can be used or two or more can be used in combination. From the viewpoint of polymerization reaction speed and polymerization rate control, it is preferred to use an azo compound or organic peroxide with a 10-hour half-life of 70 to 120°C. The amount of the polymerization initiator used is not particularly limited, and preferably 0.1 to 1.5 parts by mass is used relative to 100 parts by mass of all monomers used for polymerization, and more preferably 0.1 to 1.0 parts by mass is used. If the amount of the polymerization initiator used is 0.1 parts by mass or more, sufficient polymerization rate can be obtained, and thus it is preferred. If the amount of the polymerization initiator used is 1.5 parts by mass or less, the polymerization rate can be suppressed, and therefore the reaction is easily controlled, and the target molecular weight is easily obtained.
[0082] A chain transfer agent can be used in the manufacture of maleimide copolymers. The chain transfer agent used is not particularly limited, and examples thereof include n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, α-methylstyrene dimer, ethyl mercaptoglycolate, limonene, terpinene, etc. The amount of the chain transfer agent used is not particularly limited as long as it is within the range in which the target molecular weight can be obtained, but is preferably 0.01 to 0.8 parts by mass, and more preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of all monomers used for polymerization. If the amount of the chain transfer agent used is 0.01 to 0.8 parts by mass, the target molecular weight can be easily obtained.
[0083] The maleimide copolymer thus obtained can be used as a heat resistance imparting agent for the obtained resin composition by kneading and mixing with various resins. As various resins, there are no particular restrictions, and ABS resin, ASA resin, AES resin, and SAN resin can be cited. Since the maleimide copolymer has excellent compatibility with these resins, a high heat resistance imparting effect can be obtained. The mixing ratio of the maleimide copolymer and these resins is preferably 5 to 40% by mass of the maleimide copolymer and 60 to 95% by mass of one or more resins selected from ABS resin, ASA resin, AES resin, and SAN resin, and more preferably 10 to 30% by mass of the maleimide copolymer and 70 to 90% by mass of one or more resins selected from ABS resin, ASA resin, AES resin, and SAN resin.
[0084] When the blending ratio of the maleimide-based copolymer is within this range, the effect of improving the heat resistance of the resin composition can be obtained without reducing the chemical resistance and hue of the resin composition.
[0085] The method for mixing the maleimide copolymer with various resins is not particularly limited, and known melt mixing techniques can be used. As suitable melt mixing devices, there are screw extruders such as single screw extruders, fully meshing co-rotating twin screw extruders, fully meshing counter-rotating twin screw extruders, non- or incompletely meshing twin screw extruders, Banbury mixers, kneaders, and mixing rolls.
[0086] When the maleimide copolymer is kneaded and mixed with these resins, a stabilizer, an ultraviolet absorber, a flame retardant, a plasticizer, a lubricant, glass fiber, an inorganic filler, a colorant, an antistatic agent, etc. may be further added.
[0087] The method of obtaining the molded body from the resin composition can use known molding processing techniques, such as injection molding, extrusion molding, sheet molding, and press molding. The resin composition of the present invention has particularly excellent heat resistance and is particularly suitable for use as a material for injection molding that reaches high temperature and high pressure during the molding process.
[0088] A molded product obtained by molding the resin composition is suitable for automobile interior parts or exterior parts, etc.
[0089] Example
[0090] Hereinafter, the details will be described using examples, but the present invention is not limited to the following examples.
[0091] <Production Example of Maleimide Copolymer (A-1)>
[0092] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 6 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-1. The analysis results of the obtained maleimide copolymer A-1 are shown in Table 1.
[0093] <Production Example of Maleimide Copolymer (A-2)>
[0094] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 11 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C under stirring for 40 minutes. After the temperature was raised to 92°C, a solution prepared by dissolving 27 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 9 parts by mass of styrene were continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 30.0 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 6 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-2. The analysis results of the obtained maleimide copolymer A-2 are shown in Table 1.
[0095] <Production Example of Maleimide Copolymer (A-3)>
[0096] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C under stirring for 40 minutes. After the temperature was raised, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours while maintaining 92°C. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 8 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-3. The analysis results of the obtained maleimide copolymer A-3 are shown in Table 1.
[0097] <Production Example of Maleimide Copolymer (A-4)>
[0098] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.4 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution prepared by dissolving 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 6 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-4. The analysis results of the obtained maleimide copolymer A-4 are shown in Table 1.
[0099] <Production Example of Maleimide Copolymer (A-5)>
[0100] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.6 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 7.5 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-5. The analysis results of the obtained maleimide copolymer A-5 are shown in Table 1.
[0101] <Production Example of Maleimide Copolymer (A-6)>
[0102] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C under stirring for 40 minutes. After the temperature was raised, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours while maintaining 92°C. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was carried out for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the reaction was carried out at 140°C for 6 hours. The imidization reaction liquid after the reaction was completed was put into a vented screw extruder to remove volatile components to obtain pelletized maleimide copolymer A-6. The analysis results of the obtained maleimide copolymer A-6 are shown in Table 1.
[0103] <Production Example of Maleimide Copolymer (A-7)>
[0104] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.05 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution prepared by dissolving 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26.6 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 5.5 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer A-7. The analysis results of the obtained maleimide copolymer A-7 are shown in Table 1.
[0105] <Production Example of Maleimide Copolymer (B-1)>
[0106] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 26 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 5 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer B-1. The analysis results of the obtained maleimide copolymer B-1 are shown in Table 2.
[0107] <Production Example of Maleimide Copolymer (B-2)>
[0108] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C under stirring for 40 minutes. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 17.8 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the reaction was performed at 140°C for 5 hours. The imidization reaction liquid after the reaction was completed was put into a vented screw extruder to remove volatile components to obtain pelletized maleimide copolymer B-2. Table 2 shows the analysis results of the obtained maleimide copolymer B-2.
[0109] <Production Example of Maleimide Copolymer (B-3)>
[0110] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 19 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 6 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer B-3. The analysis results of the obtained maleimide copolymer B-3 are shown in Table 2.
[0111] <Production Example of Maleimide Copolymer (B-4)>
[0112] Into an autoclave with a capacity of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 parts by mass of tert-butyl peroxy-2-ethylhexanoate, 0.025 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl isobutyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C for 40 minutes under stirring. After the temperature was raised to 92°C, a solution of 23 parts by mass of maleic anhydride and 0.22 parts by mass of tert-butyl peroxy-2-ethylhexanoate dissolved in 50 parts by mass of methyl isobutyl ketone and 28 parts by mass of styrene were continuously added for 4.5 hours. After the addition of maleic anhydride was completed, 14 parts by mass of styrene was continuously added for 0.5 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was performed for 0.5 hours to complete the polymerization. Thereafter, 17.8 parts by mass of aniline and 0.5 parts by mass of triethylamine were added to the polymerization solution, and the mixture was reacted at 140° C. for 5 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder to remove volatile components, thereby obtaining a pelletized maleimide copolymer B-4. The analysis results of the obtained maleimide copolymer B-4 are shown in Table 2.
[0113] Table 1
[0114]
[0115] Table 2
[0116]
[0117] (Weight average molecular weight)
[0118] The weight average molecular weight of the maleimide copolymer was measured by GPC method under the following measurement conditions.
[0119] Device name: SYSTEM-21 Shodex (manufactured by Showa Denko K.K.)
[0120] Column: 3 PL gel MIXED-B connected in series
[0121] Temperature: 40℃
[0122] Detection: Differential refractive index
[0123] Solvent: Tetrahydrofuran
[0124] Concentration: 0.8 mass%
[0125] Standard curve: drawn using standard polystyrene (PS) (manufactured by PL).
[0126] (Glass transition temperature)
[0127] The glass transition midpoint temperature (Tmg) of the maleimide copolymer was measured using the following apparatus and measurement conditions in accordance with JIS K-7121.
[0128] Device name: Robot DSC6200 (manufactured by Seiko Instruments)
[0129] Heating rate: 10℃ / min
[0130] (Dicarboxylic anhydride monomer unit in one polymer molecule)
[0131] First, the content of the dicarboxylic anhydride monomer unit contained in the maleimide copolymer is measured in the following manner.
[0132] The content of the dicarboxylic anhydride monomer unit contained in the maleimide copolymer was determined by a colorimetric titration method (indicator: phenolphthalein) of a methyl ethyl ketone solution of the maleimide copolymer with a 0.1 N ethanolic potassium hydroxide solution.
[0133] A: Mass of maleimide copolymer (g)
[0134] B: Blank value of the volume of the added ethanolic potassium hydroxide solution (mL)
[0135] C: Volume of ethanolic potassium hydroxide solution added (mL)
[0136] D: molar mass of dicarboxylic anhydride monomer unit,
[0137] The content (mass %) of the dicarboxylic anhydride monomer unit contained in the maleimide copolymer was determined by the following formula.
[0138] Content ratio of dicarboxylic anhydride monomer unit (F) = (CB) × D / A / 100
[0139] Next, the average value of the dicarboxylic anhydride monomer units in one molecule of the maleimide-based copolymer is calculated from the value of the weight average molecular weight (E) calculated above by the following formula.
[0140] Average value of dicarboxylic anhydride monomer units in one molecule of maleimide copolymer = E×F / D / 100
[0141] <Examples and Comparative Examples>
[0142] Examples 1 to 7, Comparative Examples 1 to 4 (Mixed and kneaded maleimide copolymer and ABS resin)
[0143] The maleimide copolymers A-1 to A-7, B-1 to B-4 were mixed with the commercially available ABS resin "GR-3000" (manufactured by Denka Co., Ltd.) in the proportions shown in Tables 3 and 4, and then extruded and pelletized using a twin-screw extruder (TEM-35B manufactured by Toshiba Machine Co., Ltd.). The pellets were used to form test pieces using an injection molding machine, and the physical properties were measured. The results are shown in Tables 3 and 4.
[0144] Table 3
[0145]
[0146] Table 4
[0147]
[0148] (Charpy impact strength)
[0149] According to JIS K-7111, notched test pieces were used, and the impact direction was edgewise impact, and the measurement was performed at a relative humidity of 50% and an ambient temperature of 23° C. The measurement instrument used was a digital impact tester manufactured by Toyo Seiki Seisaku-sho., Ltd.
[0150] (Vicat softening point)
[0151] The test was conducted using a 10 mm x 10 mm, 4 mm thick test piece using the 50 method (load 50 N, heating rate 50°C / hour) according to JIS K7206. The HDT & VSPT tester manufactured by Toyo Seiki Seisaku-sho Co., Ltd. was used as the measuring instrument.
[0152] (Melt mass flow rate; MFR)
[0153] The measurement was performed at 220°C and a load of 98N in accordance with JIS K 7210.
[0154] (Glossiness)
[0155] The measurement was performed at a measurement angle of 60° in accordance with JIS Z-8741. As the measuring instrument, UGV-4D manufactured by Suga Test Instruments Co., Ltd. was used.
[0156] For the maleimide copolymers A-1 to A-7 that meet the scope of the present invention, the number of dicarboxylic anhydride monomer units contained in these copolymers is sufficiently small and the glass transition temperature is sufficiently high, so the resin compositions of Examples 1 to 7 obtained by mixing these maleimide copolymers with ABS resin have good impact resistance, fluidity, heat resistance, and surface gloss. In addition, since the matrix resin of ABS resin is AS resin, the maleimide copolymer of the present invention can also be expected to impart the same effect to AS resin, AES resin and ASA resin using AS resin as the matrix resin. On the other hand, the resin compositions of Comparative Examples 1 to 4 obtained by mixing maleimide copolymers B-1 to B-4 that do not meet the scope of the present invention with ABS resin have poor fluidity, heat resistance, and surface gloss.
[0157] Industrial Applicability
[0158] The maleimide copolymer of the present invention can be mixed with ABS resin, ASA resin, AES resin and SAN resin to obtain a resin composition having excellent balance of heat resistance, impact resistance, fluidity and surface gloss. The obtained resin composition is suitable for use as a material for automobile interior parts or exterior parts.
Claims
1. A maleimide copolymer comprising 40 to 60% by weight of an aromatic vinyl monomer unit, 7 to 20% by weight of a vinyl cyanide monomer unit, 25 to 50% by weight of a maleimide monomer unit, and 0.1 to 10% by weight of a dicarboxylic anhydride monomer unit. The glass transition temperature of the maleimide copolymer is 165° C. to 200° C., and the average number of dicarboxylic anhydride monomer units contained in one molecule of the copolymer is 1 to 20.
2. The method for producing a maleimide-based copolymer according to claim 1, comprising the following steps: Initial polymerization step: mixing the entire amount of vinyl cyanide monomer, 10 to 90% by weight of aromatic vinyl monomer, and 0 to 30% by weight of unsaturated dicarboxylic anhydride monomer to initiate copolymerization; Mid-term polymerization step: adding 50-90% by weight of the remaining aromatic vinyl monomer and all of the remaining unsaturated dicarboxylic anhydride monomer in batches or continuously, and continuing copolymerization; Final polymerization step: adding all the remaining amount of the aromatic vinyl monomer to obtain a copolymer having an aromatic vinyl monomer unit, a cyanide vinyl monomer unit, and a dicarboxylic anhydride monomer unit; and Imidization step: The dicarboxylic anhydride monomer units of the obtained copolymer are imidized to maleimide monomer units using ammonia or a primary amine.
3. A resin composition comprising 5 to 40% by mass of the maleimide copolymer according to claim 1 and 60 to 95% by mass of a resin, The resin is one or more selected from acrylonitrile-butadiene-styrene copolymer resin, acrylonitrile-styrene-acrylic rubber copolymer resin, acrylonitrile-ethylene·propylene rubber-styrene copolymer resin or styrene-acrylonitrile copolymer resin. 4 . An injection-molded article using the resin composition according to claim 3 . The injection molded article according to claim 4 , which is used as an interior part or exterior part of an automobile.
Citation Information
Patent Citations
Heat-resistant resin composition
JP1982098536A
Thermoplastic resin composition
JP1982125242A
Maleimide resin composition
JP2004339280A
Thermoplastic copolymer and manufacturing method thereof
JP2007009228A
Method for preparing imide substituted copolymer resin
CN1854160A